Reconstruction of the Anterior Cruciate Ligament and the Posterolateral Corner With a Single Combined Femoral Tunnel - Andre Giardino Moreira da Silva MD; Riccardo Gomes Gobbi MD, PhD; Marcelo Batista Bonadio MD, PhD; Fabio Janson Angelini MD, PhD; José Ricardo Pécora MD, PhD; Camilo Partezani Helito MD, PhD (Video Journal of Sports Medicine)
Background: Posterolateral knee injuries can occur in 16% of patients with acute ligament injuries, and up to 70% have a combined anterior cruciate ligament (ACL) tear. Studies have shown that, in different populations, the distance between the insertion of the popliteus tendon and the lateral collateral ligament (LCL) may be smaller than the 18.5 mm previously reported in the literature. When we have an associated injury of the ACL and the posterolateral corner (PLC), the confluence of tunnels in the lateral femoral condyle can be a potential problem during reconstruction surgery. Indications: The indication of this technique is the combined injury of the ACL and the PLC. Technique Description: The reconstruction is performed with 2 semitendinosus tendons and 1 gracilis tendon. The technique consists of making a tunnel in the lateral wall of the femur, from the outside-in, at the isometric point between the origin of the LCL and insertion of the popliteus tendon, and emerging in the inner wall of the lateral femoral condyle at the anatomic point of the ACL. The graft is passed from the tibia to the femur with the doubled gracilis tendon and the 2 simple semitendinosus tendons for the ACL graft. The remaining portions of the semitendinosus tendons are left for reconstruction of the PLC structures, with one of them going straight to the posterolateral tibial tunnel (reconstructing the popliteus tendon), and the other passing through the fibular head tunnel (reconstructing the LCL) and continuing from the fibular head to the posterolateral tibial tunnel (reconstructing the popliteofibular ligament). Results: Patients undergoing this technique achieved good functional outcomes and a failure rate similar to that reported in the literature for combined ACL and PLC reconstruction. Discussion/Conclusion: This technique is an excellent option for patients with the combined injury of the ACL and the PLC, avoiding the confluence of tunnels in the lateral femoral condyle. It presents good results and acceptable complication rates, compatible with the severity of this lesion. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.